DEVELOPING COMMUNICATION COMPETENCIES OF UNIVERSITY STUDENTS IN THE CREDIT-MODULE SYSTEM (International journal of artificial intelligence, 2025)
This article explores the pedagogical possibilities of developing communication competencies of future teachers in the context of the credit-module system. It provides an in-depth explanation of the credit-module system, its potential, and its importance in developing students' communication competence. Definitions of the content of communication competence are also provided.